Pattern of ABO and Rhesus(Rh) Blood Group Among Blood Donors - Ahad, MA; Bakar, MA (TAJ: Journal of Teachers Association, 2009)
This study was carried out among the blood donors attending the Blood Transfusion Department of Khulna Medical College Hospital. Both ABO and Rhesus (Rh) blood grouping was done to see the pattern of ABO and Rh blood group among them. Maximum blood donors were between age group 18-37 years. Among the donors maximum were male 12105 (94.73%). Male: female ratio was 18:1. Among them B+ve was found 4286 (33.54%), B-ve was 127 (5.0%), O+ve was 4091 (32.02%), O-ve was 131 (1.03%), A+ve was 3014 (23.59%), A-ve was 74 (0.58%), AB+ve was 1019 (7.98%), AB-ve was 37 (0.29%). Overall total Rh positive blood group were 12410 (97.11%) and total negative blood group were 369 (2.89%). doi: 10.3329/taj.v15i2.3910 TAJ December 2002; Vol.15(2): 68-70